Pneumonia Clinical Features in Under-Five Children Treated in Atma Jaya Hospital in 2017-2020 - Rachel Roselany; Edward Surjono (Faculty of Medicine, Universitas Padjadjaran, 2023)
Pneumonia is the leading cause of infection-related death among children and still remains a global health problem, especially for children under five. This study aimed to identify the clinical features of pneumonia in under-five chilren treated at Atma Jaya Hospital during the period of 2017-2020. This was a cross-sectional retrospective descriptive study on all under-five patients diagnosed with pneumonia treated in Atma Jaya Hospital. Data were collected from November 2021-January 2022 from the medical records of these children (n=148) and analyzed using the univariate analysis. Results showed that most subjects of this study were boys (60.8%), in the age group of 1-4 years old (62.2%), with fever as the most common pnemonia clinical symptom (93.9%). Physical examinations revealed that the average pulse of the subjects were 131.2 beats/minute and the average temperature was 37.1°C. Other signs and symptoms identified during physical examinations were tachypnea (20,3%), retractions (56.1%), crackles (82.4%), and wheezing (22,3%). The laboratory findings presented a mean hemoglobin of 11.0 g/dL, a mean hematocrit of 32.5%, and a mean CRP of 13.2 mg/dL, while most subjects had normal leukocyte (58.1%) and platelet counts (52.0%). The most common chest X-ray finding of pneumonia in these children was infiltrate (92.6%) and the average length of stay was 4 days. Most under-five children experiencing pneumonia recovered after treatment (97.3%).